An Instructional Analysis of the 10th Grade Textbook Entitled “English for Critical Thinking” Using Revised Bloom’s Taxonomy - Fatwadika Adinia Dakoranis; Sri Wahyuni (Universitas Negeri Semarang, 2025)
Several previous studies that conducted textbook evaluations still found many shortcomings, imbalances, and inadequate content with their claims and misalignment with the curriculum objectives. In addition, many textbook evaluations of HOTS focused on reading comprehension and the main textbook. This study, therefore to fill the gaps, aimed to (1) classify all exercise instructions in the textbook entitled “English for Critical Thinking” Grade 10th into Lower-Order Thinking Skills (LOTS: C1–C3) and HOTS (C4–C6) based on Revised Bloom’s Taxonomy, and (2) identify which HOTS category was most prevalent. Employing a qualitative content-analysis approach, the researcher systematically reviewed and coded 57 instructional items across the twelve chapters, assigning each to its respective Revised Bloom’s Taxonomy cognitive level. Findings reveal that LOTS dominated 82.45% of all instruction exercises, while HOTS comprised only 17.54%. Within the HOTS domain, analyzing (C4) was overwhelmingly the most frequent with eight occurrences (80%), whereas evaluating (C5) and creating (C6) appeared only once each (10% each). This imbalance indicates that, although C4 tasks are fairly represented, higher cognitive processes of evaluation and creation remain severely under implemented. Consequently, the textbook’s purported support for critical and creative thinking does not fully align with Merdeka Curriculum objectives. Therefore, textbook developers and teachers should enrich future editions with more evaluative and creative tasks and ensure a balanced cognitive progression to develop students’ HOTS optimally.